Effect of Epidemic Intermittent Fasting on Cardiometabolic Risk Factors: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Yang, Fan; Liu, Can; Liu, Xu; Pan, Xiandu; Li, Xinye; Tian, Li; Sun, Jiahao; Yang, Shengjie; Zhao, Ran; An, Na; Yang, Xinyu; Gao, Yonghong; et al. (Frontiers in Nutrition, 2021)
Intermittent fasting (IF) has gained attention as a promising diet for weight loss and dysmetabolic diseases management. This systematic review aimed to investigate the effects of IF on cardiometabolic risk factors (CMRFs). A systematic literature search was carried out using three electronic databases, namely PubMed, Embase, and the Cochrane Library, until October 2020. Randomized controlled trials that compared the IF intervention with a control group diet were included. Fourteen effect sizes were expressed as weighted mean difference (WMD) using a fixed-effects model and 95% confidence intervals (CI). Compared to the ones within control groups, participants exposed to the IF intervention reduced their body weight (WMD, -1.78 kg; 95% CI, -2.21 to -1.35; p < 0.05), waist circumference (WMD, -1.19 cm; 95% CI, -1.8 to -0.57; p < 0.05), fat mass (WMD, -1.26 kg; 95% CI, -1.57 to -0.95; p < 0.05), body mass index (WMD, -0.58 kg/m2; 95% CI, -0.8 to -0.37; p < 0.05), systolic blood pressure (WMD, -2.14 mmHg; 95% CI: -3.54 to -0.73; p < 0.05), diastolic blood pressure (WMD: -1.38 mmHg, 95% CI, -2.35 to -0.41, p < 0.05), fasting blood glucose (WMD: -0.053 mmol/L; 95% CI: -0.105 to 0.001; p < 0.05), fasting insulin (WMD, -0.8 mIU/L; 95% CI, -1.15 to -0.44; p < 0.05), insulin resistance (WMD, -0.21; 95% CI, -0.36 to -0.05; p < 0.05), total cholesterol (WMD, -0.10 mmol/L; 95% CI,-0.17 to -0.02; p < 0.05), and triglycerides (WMD, -0.09 mmol/L; 95% CI, -0.13 to -0.04; p < 0.05). No effects were observed for low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, or glycosylated hemoglobin. This meta-analysis supports the role of IF in improving the component composition of CMRFs, including weight, waist circumference, fat mass, BMI, blood pressure, total cholesterol, triglycerides, fasting insulin, and insulin resistance, compared to a control group diet. Further research on IF interventions should take into account long-term and well-designed administration to draw definitive conclusions.